Antibiotic Consumption Trends in China: Evidence From Six-Year Surveillance Sales Records in Shandong Province - Song, Yan; Han, Zhiyan; Song, Kuimeng; Zhen, Tianmin (Frontiers in Pharmacology, 2020)
Background: The overuse of antibiotics is a serious public health problem in China, causing a high rate of antimicrobial resistance. This study identified the trends of antibiotic consumption in China to provide evidence for further intervention. Method: The six-year surveillance data on antibiotic sales from 2012 to 2017, which served as a proxy for consumption, were collected from 39 public health care facilities in Shandong province, including three tertiary hospitals, six secondary hospitals, and 30 primary health centers. Based on the Anatomical Therapeutic Chemical (ATC)/DDD methodology, antibiotic consumption was formulated in defined daily doses (DDD) per 1,000 inhabitants per day (DID). Results: The total antibiotic consumption among all health care settings increased from 16.07 DID in 2012 to a peak of 17.44 DID in 2015 and then decreased to 11.35 DID in 2017 with a 34.90% reduction. J01C (beta-lactam antimicrobials, penicillins), the most frequensntly used antibiotic class, accounted for 36.32% of the total DID. Consumption of carbapenems increased from 0.029 DID in 2012 to 0.08 DID in 2017. Parenteral antibiotics accounted for nearly 40% of the total consumption. Compared with the 2012 figures, the 2017 consumption showed a small increase in hospital sector that was compensated by the decrease in community care. Conclusion: A substantial reduction in total antibiotic consumption was observed in China from 2012 to 2017. However, the extensive consumption of broad-spectrum antimicrobials, high proportion of parenteral antibiotic use, and increased use of last-resort antibiotics attracted public health concerns.